(untitled) (Biodiversitas Journal of Biological Diversity, 2010)
Meshram PM (2010) Diversity of some fauna in National Chambal Sanctuary in Madhya Pradesh, India. Biodiversitas 11: 211-215. National Chambal Sanctuary (NCS) gives very good account of avifauna. It over emphasizes significant and important birds species available which are of National and International importance. Crocodiles use sand banks for nesting and basking. Fauna in the NCS is very much influenced by various factors like habitat suitability and protection of their habitats. Their distribution is depending on availability of deep water pools. Another important factors on which distribution of animals depends long stretches of long sand banks. Sloppy to steep sand bank with loose soil were good habitats for nesting of crocodiles, turtles and birds. NCS areas were considerably altered and there were disturbance by the sand miners, poachers, fishermen and farmers. Consequently the poor survival is recommended to greater protection by management practices. Effective co-operations between the Forest Department of Madhya Pradesh and neighbouring states were needed as sand mining and poaching becomes an interstate problem. Thus, strategic location of this site in the migratory route of water birds enhances its importance as a significant water bird habitat. In the present study diversity of some fauna in NCS is discussed. Key words: National Chambal Sanctuary, fauna, diversity